Pengaruh Promosi dan Harga Terhadap Minat Beli Konsumen di Aplikasi Shopee di Kota Bekasi - Anwar, Rifky; W, Warsono (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The background of this study is based on the rapid growth of e-commerce in Indonesia and the increasing use of Shopee in Bekasi City, which reached 25% in 2023. This research employs a quantitative approach by distributing questionnaires to Shopee consumers in Bekasi City. The study aims to examine the effect of promotion and price on consumer purchase intention in the Shopee application in Bekasi City. Since the population in Bekasi City is infinite, the sampling technique used the Lemeshow formula, resulting in a sample of 100 respondents. The research applied quantitative statistical methods with tests including data quality, classical assumption, hypothesis testing, and the coefficient of determination. The results of the study show that promotion has a significant partial effect on consumer purchase intention in the Shopee application in Bekasi City; therefore, Ho1 is rejected and Ha1 is accepted. Price also has a significant partial effect on consumer purchase intention in the Shopee application in Bekasi City; therefore, Ho2 is rejected and Ha2 is accepted. Furthermore, promotion and price simultaneously have a significant effect on consumer purchase intention in the Shopee application in Bekasi City; therefore, Ho3 is rejected and Ha3 is accepted.